Preoperative PET/CT does not accurately detect extrauterine disease in patients with newly diagnosed high‐risk endometrial cancer: A prospective study. Issue 19 (21st June 2019) - Stewart, Katherine I.; Chasen, Beth; Erwin, William; Fleming, Nicole; Westin, Shannon N.; Dioun, Shayan; Frumovitz, Michael; Ramirez, Pedro T.; Lu, Karen H.; Wong, Franklin; Aloia, Thomas A.; Soliman, Pamela T.
Abstract : Background: The identification of extrauterine disease is critical to the management of patients with high‐risk endometrial cancer. The purpose of the current study was to determine the accuracy of preoperative positron emission tomography (PET)/computed tomography (CT) in the detection of extrauterine disease. Methods: Women with high‐risk endometrial cancer were enrolled prospectively and underwent preoperative PET/CT followed by surgery, including sentinel lymph node biopsy and lymphadenectomy. Primary tumor factors on PET/CT were correlated with lymph node pathology. The sensitivity, specificity, positive predictive value, and negative predictive value were calculated for the detection of lymphadenopathy and peritoneal disease by PET/CT. Results: A total of 112 patients were enrolled and underwent PET/CT between April 2013 and May 2016, 108 of whom were evaluable. On PET/CT, 21 patients (19.4%) were found to have extrauterine disease, 18 (17%) had positive lymph nodes, and 8 (7%) had peritoneal disease. A total of 108 patients underwent surgery, 103 of whom (95%) underwent lymphadenectomy. The sensitivity of PET/CT to detect positive lymph nodes was 45.8%, with a specificity of 91.1%, positive predictive value of 61.1%, and negative predictive value of 84.7%. The false‐negative rate was 54.2%. There was no difference in primary tumor characteristics on imaging noted between patients with positive and negative lymph nodes. The sensitivity of PET/CT to detect peritoneal disease was 37.5%, with a specificity of 97.8%, positive predictive value of 75%, and negative predictive value of 90.0%. The false‐negative rate was 62.5%. Conclusions: Preoperative PET/CT did not reliably predict the presence of extrauterine disease in women with high‐risk endometrial cancer. Given the high false‐negative rates, PET/CT should not be used in the preoperative treatment planning of these patients. Abstract : Preoperative positron emission tomography (PET)/computed tomography (CT) does not reliably predict extrauterine disease in women with high‐risk endometrial cancer. PET/CT should not be used in the preoperative treatment planning in patients with high‐risk endometrial cancer.